Decision Making: Osteoplasty, Ablation, or Combined Therapy for Spinal Metastases - Lea, William; Tutton, Sean (Seminars in Interventional Radiology, 2017)
Metastatic disease involving the spine and pelvis is common, often resulting in significant pain and disability. Several percutaneous interventions have been described, including osteoplasty, ablation, and screw fixation, that when used alone or in combination can significantly reduce pain and disability from metastatic bone disease. Although it is possible to make a significant impact in patient care with basic principles and techniques, certain advanced techniques can extend the application of percutaneous interventions while minimizing morbidity.
Keywords: vertebroplasty; ablation; metastases; bone; interventional radiology